Bibliotherapy in a School Context - Đorđević, Mirjana V.; Glumbić, Nenad P.; Brojčin, Branislav B. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The goal of bibliotherapy is to use a book to help the reader understand and overcome the difficulties he or she is facing. It can be applied in different contexts. If it is applied in a school environment, we are talking about developmental bibliotherapy.The aim of this paper is to describe the basic stages of developmental bibliotherapy, to present the results of research that indicate the effectiveness of its application, as well as the results of research that refer to the inclination of teachers and associates to opt for this technique.Given that this technique is considered to be a simple, cost-effective, and efficient intervention, and that some teachers and associates do not venture to apply it because they lack the necessary knowledge and skills, the inclusion of bibliotherapy in college training programs could contribute to the increased readiness of professionals to use it in order to help children face challenges in a developmentally appropriate manner.
Keywords: teachers; developmental bibliotherapy; use of book